The use of controlled vocabulary to combat organized crime in the Federal Police - Bispo, Fabrício Dantas; Vital, Luciane Paula (Advanced Notes in Information Science, 2023)
Implementing a controlled vocabulary in institutional information retrieval tools in the Federal Police of Brazil can overcome the barriers of linguistic diversity associated with formal and informal language, improving the accuracy and quality of investigation results. This work highlights the importance of using knowledge organization systems inefficiently to recover large volumes of data, especially from investigations, to combat organized crime and combined with automated processing. Using these systems, it is intended that all information relevant to an investigation is retrieved. The vocabulary controlled by the Federal Police, integrated with the information retrieval tools, becomes essential to qualify this retrieval, giving precision to criminal investigation work.